THE CRISIS OF NON-SYSTEM OPPOSITION: A TREND OR AN ACCIDENT? - N. P. Pimenov (Дискурс)
The article describes non-system opposition as an active participant of political communication in modern Russia. Its brief description is given - the main stages of the development, direction, parties. An ordinary protester is described with the help of sociological research data and waning popularity of the non-system opposition representatives is demonstrated. The paper explains the crisis causes, identifies events patterns and estimates prospects.